THE MARKET REACTION IN THE MANUFACTURING SECTOR SHARE TO THE EVENT OF THE APPROVAL OF THE JOB CREATION LAW IN 2020 - Irianing Suparlinah; Yusrizal Karunia; Negina Kencono Putri; Adi Wiratno (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
This study aims to determine the Market Reaction in Manufacturing Sector Stocks to the Legalization of the Job Creation Law 2020. The purposive sampling technique was used from all manufacturing companies listed on the Indonesia Stock Exchange for the 2020 period. The event study analysis technique was used in this study with an observation period of approx. 21 trading days (10 days before and 10 days after). The results of statistical tests on abnormal returns show that there is no significant difference in the average abnormal return before and after the event and indicates a semi-strong form of market efficiency. The results of statistical tests on trading volume activity show that there is a significant difference in average trading volume activity before and after the event. This study implies that the ratification of the Job Creation Law has an impact on the investment climate so that when major political events occur, it is hoped that market participants will be more careful in making investment decisions, especially in buying and selling shares.